Revolution as Realpolitik : Ernst Meyer (1887-1930) - Biography of a KPD Chairman - Wilde, Florian, (Historical Materialism Book Series ;, 2026)
Ernst Meyer was one of the most important figures of the German Communist Party in the Weimar Republic. He was a founding member of the Spartacus League, a member of the KPD Centre after the First World War and party chairman in 1921-22. A passionate defender of the necessity of inner-party democracy against the "ultra-left" leadership around Ruth Fischer and later the Thälmann Central Committee, as well as a supporter of revolutionary realpolitik, Meyer played a significant role in the development of the communist united front strategy and, as a critic of Stalin, later argued against the disastrous thesis of "social fascism". Despite this, Meyer has largely been forgotten. Florian Wilde now traces for the first time the political and private life and work of this disciple of Rosa Luxemburg, highlighting the strategic debates within the KPD and the alternatives to its Stalinisation, inherent in the development of the party.